2006
DOI: 10.1167/iovs.05-1639
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Abnormalities in Patients with Primary Open-Angle Glaucoma

Abstract: These results reveal a spectrum of mitochondrial abnormalities in patients with POAG, implicating oxidative stress and implying that mitochondria dysfunction may be a risk factor for POAG. This concept may open up new experimental and therapeutic opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
229
1
13

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(256 citation statements)
references
References 43 publications
13
229
1
13
Order By: Relevance
“…9,22 Mitochondrial dysfunction and mtDNA defects have been implicated in RGC loss and the development of glaucoma. 7,10,22,23 The expansion of massively parallel sequencing has revolutionized mitochondrial genetics. [24][25][26] Sanger sequencing has long been considered the gold standard for molecular diagnosis of mtDNA-based disorders.…”
Section: Discussionmentioning
confidence: 99%
“…9,22 Mitochondrial dysfunction and mtDNA defects have been implicated in RGC loss and the development of glaucoma. 7,10,22,23 The expansion of massively parallel sequencing has revolutionized mitochondrial genetics. [24][25][26] Sanger sequencing has long been considered the gold standard for molecular diagnosis of mtDNA-based disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that a maternal family history is more frequent than a paternal history in glaucoma [13-16] which suggests a contribution of mitochondrial DNA (mtDNA) to glaucoma pathogenesis. In fact, an increased frequency of nonsynonymous mtDNA sequence changes in patients with primary open angle glaucoma has been shown [17]. However, this report describes a relatively small number of patients from a restricted ethnic population and confirmation in other populations is still lacking.…”
Section: Introductionmentioning
confidence: 86%
“…A significant correlation between oxidative DNA damage in the trabecular meshwork and intraocular pressure (IOP) increase and visual field defects was observed in glaucomatous patients [10]. In an independent study, a significant reduction of mitochondrial respiratory function in peripheral blood cells was observed in glaucoma patients when compared to age-matched healthy controls [11]. Another study showed that the exposure of RGCs to elevated hydrostatic pressure resembling an elevated intraocular pressure results in altered mitochondrial fission [12].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of mitochondrial dysfunction in glaucoma (Mittag et al, 2000;Tatton et al, 2001;Tezel and Yang, 2004); and as summarized in section 3, mitochondrial dysfunction critically participates in RGC death (Tezel and Yang, 2004). By demonstrating mitochondrial DNA abnormalities, a recent study also implicates mitochondrial dysfunction-associated oxidative stress as a risk factor for glaucoma patients (Abu-Amero et al, 2006). In addition to somal death, mitochondrial dysfunction likely contributes to compartmentalized neurodegenerative processes in glaucoma.…”
Section: Oxidative Stress In Widespread Damage To Rgcs In Glaucomamentioning
confidence: 99%